Exploring the effects of acute digital sports dance intervention on children's gross motor development, executive function, and muscle coordination using electromyography sensors: a randomized repeated-measures study - He, J.; Zhao, J.; Li, H.; Chen, J.; Qin, Y. (Sensors, 2025)
Objective: This paper examines how rhythm-enhanced digital dance affects children`s motor abilities, cognitive performance, and neuromuscular synchronization. Methods: In a randomized repeated-measures study, 38 children (7-12 years) underwent three conditions: groove music-accompanied dance (GODA), conventional music dance (CODA), and non-musical physical activity (CON). Assessments of gross motor skills (using TGMD-3), executive function (using BRIEF and Stroop Test), and muscle coordination (using sEMG) were conducted. Results: Gross motor skills: GODA showed significantly higher TGMD scores in locomotor (p = 0.03) and ball skills (p = 0.02) compared to both CODA and CON (p < 0.001). Executive function: Inhibition and shifting dimensions showed significant post-intervention condition differences (p < 0.05). Muscle coordination: GODA exhibited greater ß- and gamma-band COH areas in the standing long jump compared to both CODA (p = 0.02) and CON (p < 0.001), and increased gamma-band COH areas in single-leg balance compared to CODA (p = 0.02) and CON (p < 0.001). Conclusions: Combining rhythmic auditory stimulation with movement training offers a promising approach for integrated motor-cognitive development in children.